Evaporative cooling in ATLAS-Present and future - Viehhauser, G; Collaboration, ATLASID (2011)
The ATLAS Inner Detector cooling system is the largest evaporative cooling system used in High Energy Physics today. During the installation and commissioning of this system many lessons had to be learned, but the system is now operating reliably, although it does not achieve all original design specifications in all its circuits. We have re-evaluated the requirements for the cooling system for the barrel SCT, in particular for the evaporation temperature, over the full ATLAS operational lifetime. We find that the critical requirement is for thermal stability at the end of LHC operation. To predict this we have developed a simple thermal model of the detector modules which yields analytical expressions to evaluate the results of changes in the operating conditions. After a comparison of the revised requirements and the actual present cooling system performance we will discuss various modifications to the system which will be required for future operation. In parallel we are developing a cooling system for the ATLAS phase II upgrade (sLHC) tracker, for which a set of requirements has been specified. Two technologies, based on different coolants, fluorocarbons or CO2, are being pursued. © 2010 Elsevier B.V. All rights reserved.